Inovasi Teknologi Finansial (Fintech) dalam Pengelolaan Keuangan Institusi Pendidikan Islam - Yusuf, M. (Diksi: Jurnal Pendidikan dan Literasi, 2023)
Islamic educational institutions play a vital role in shaping quality and integrity in the younger generation. However, a common issue faced by these institutions is the efficient and transparent financial management. This article presents financial technology (fintech) innovation as a potential solution to address the challenges in financial management within Islamic educational institutions. The background highlights the importance of proper financial management to support quality educational operations. The research aims to analyze the concept of fintech in the context of financial management in Islamic educational institutions, explore fintech utilization models, and evaluate related regulatory and security implications. The research methodology employed is a literature review, involving the analysis of various theoretical sources, studies, and reports related to fintech in the context of Islamic education. The research findings demonstrate that fintech offers various benefits, such as efficient student fund management, funding diversification, and financial transparency. Nevertheless, challenges need to be addressed, including data security, regulatory compliance, and institutional readiness to adopt this technology. By implementing financial technology innovations, Islamic educational institutions can enhance efficiency, transparency, and accessibility in their financial management, thus supporting the achievement of more optimal educational goals.   Keywords: Innovation, fintech, financial management, Islamic educational institutions.   Abstrak Institusi pendidikan Islam memiliki peran vital dalam membentuk generasi berkualitas dan berintegritas. Namun, isu umum yang dihadapi institusi ini adalah pengelolaan keuangan yang efisien dan transparan. Artikel ini menyajikan inovasi teknologi finansial (fintech) sebagai solusi potensial untuk mengatasi tantangan dalam pengelolaan keuangan di institusi pendidikan Islam. Latar belakang menyoroti pentingnya pengelolaan keuangan yang tepat guna guna mendukung operasional pendidikan yang berkualitas. Tujuan penelitian adalah untuk menganalisis konsep fintech dalam konteks pengelolaan keuangan institusi pendidikan Islam, mengeksplorasi model penggunaan fintech, serta mengevaluasi implikasi regulasi dan keamanan yang terkait. Metode penelitian yang digunakan adalah studi literer, yang melibatkan analisis berbagai sumber teori, penelitian, dan laporan terkait fintech dalam konteks pendidikan Islam. Hasil penelitian menunjukkan bahwa fintech memberikan berbagai manfaat, seperti pengelolaan dana siswa yang efisien, diversifikasi pendanaan, dan transparansi keuangan. Namun, terdapat tantangan yang harus diatasi, termasuk keamanan data, kepatuhan regulasi, dan kesiapan institusi dalam mengadopsi teknologi ini. Dengan menerapkan inovasi teknologi finansial, institusi pendidikan Islam dapat meningkatkan efisiensi, transparansi, dan aksesibilitas dalam pengelolaan keuangan mereka, sehingga mendukung tercapainya tujuan pendidikan yang lebih optimal.